The Quest(ioning) of Epistemological Ground: The Spanish Generation of 1956 - Judith Nantell (Studies in 20th & 21st Century Literature, 1992)
Much of the critical literature written about the poetry of the Generation of 1956 asserts that for Claudio Rodriguez, José Angel Valente and Francisco Brines, among other members of this group, writing poetry is a means to knowledge. Knowledge, however, exists in tension with its apparent opposite, ignorance. Because the supplement ruptures the tidy arrangement of the knowledge/ignorance polarity, it is no longer possible to focus on either entity in isolation. If knowledge and ignorance continually imply one another, then Valente's famous dictum, "todo poema es un conocimiento haciéndose" ('every poem is knowledge becoming') which has long served as the foundation both of this generation and the critical literature written about this generation, itself is reconstituted in terms of ignorance. In scrutinizing selected poems of these poets, the critic discerns that poetry is not a process of knowing but rather a method for questioning epistemological ground. As this essay demonstrates, both the poetic text and the interpretive text investigate knowledge and ignorance, forever "becoming" their own différance.
Keywords: Generation of 1956; Claudio Rodriguez; José Angel Valente; Francisco Brines; knowledge; poetry; ignorace; critical literature; questioning; becoming; self; différance